The Effect of Leadership and Work Environment on Employee Performance with Employee Motivation Intervening Variables at PT. Lezax Nesia Jaya - Emmy Widiastuti; Arif Hartono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purpose of this study is to analyze the role and influence of leadership, work environment on employee performance with the intervening variable of employee motivation at PT. Lezax Nesia Jaya. Data were collected using a questionnaire and using a Likert scale 1 - 6. The research method was carried out by the census method on all employees of PT. Lezax Nesia Jaya as many as 344 employees. Questionnaires that can be processed and analyzed as many as 282. Data processing and analysis were carried out using multiple linear regression analysis and path analysis methods. The device used uses SPSS software. The results showed that leadership had a positive and significant effect on employee motivation. The work environment has a positive and significant effect on employee motivation. Leadership has no effect on employee performance. The work environment has a positive and significant effect on employee performance. Employee motivation has no effect on employee performance. Leadership has no positive and significant effect on employee performance through employee motivation. The work environment has no effect on employee performance through employee motivation.